Persepsi Istri Jama’ah Tabligh Tentang Pemenuhan Nafkah Saat Khuruj (Studi pada Masyarakat Jama’ah Tabligh di Kelurahan Perdamaian Kecamatan Stabat Kabupaten Langkat) - Radhwa, Hafidza (Jurnal Landraad, 2024)
Jama'ah Tabligh is a religious movement that has the concept of movement and tabligh. In carrying out da'wah, the Tabligh Jama'ah usually has an activity commonly known as khuruj, where this khuruj activity is carried out by traveling topreach for 3 days, 10 days, 40 days, 4 months to years. The implementation of khuruj is inseparable from the responsibility of the husband as the head of the family in fulfilling physical and mental nafkah and nakah for his children. This research focuses on the wives of members of the Tabligh Jama'ah in Peace Village, Stabat District, Langkat Regency. The author wants to see how the fulfillment of nafkah in the tabligh jama'ah family, how the wife's perception of the fulfillment of nafkah received from her husband as a member of the tabligh jama'ah while being khuruj, and how Islamic law reviews the fulfillment of nafkah husband-wife. To answer these questions, the author conducted research with a type of field research (field research) which is descriptive qualitative. The data sources used in this study consist of primary and secondary data sources. Data collection techniques are carried out by interview and documentation. And the data analysis used in this research is a qualitative field analysis method, because the data obtained is information in the form of descriptions from written sources or expressions of observed behavior. The results of this study are: First, the fulfillment of maintenance for members of the Tabligh Jama'ah is that before they carry out khuruj activities, they must first provide maintenance to their wives and children. The amount of maintenance given must meet the needs of the family left behind. Second, regarding the wife's perception as long as the husband always fulfills his wife and children's livelihood, then the wife certainly approves of her husband's activities. Third, when viewed from Islamic law, as long as family maintenance is carried out and fulfilled properly, and the husband does not neglect his responsibilities and obligations, then there is nothing contrary to Islamic law regarding khuruj carried out by the Tabligh jama'ah.